Association of maternal CNVs in GSTT1/GSTT2 with smoking, preterm delivery, and low birth weight - Zheng, Xiaojing; Feingold, Eleanor; Ryckman, Kelli K.; Shaffer, John R.; Boyd, Heather A.; Feenstra, Bjarke; Melbye, Mads; Marazita, Mary L.; Murray, Jeffrey C.; T.Cuenco, Karen (Frontiers in Genetics, 2013)
Preterm delivery (PTD) is an adverse birth outcome associated with increased infant mortality and negative lifelong health consequences. PTD may be the result of interactions between genetics and maternal/fetal environmental factors including smoking exposure (SMK). A common deletion in the GSTT1 gene was previously reported to affect birth outcomes in smokers. In this study, we dissect the associations among SMK, birth outcomes, and copy number variations (CNVs) in the GSTT1/GSTT2 region. A preterm birth case-control dataset of 1937 mothers was part of the GENEVA preterm birth study, which included genome-wide genotyping used to identify CNVs. We examined the association of SMK with birth outcomes, detected CNVs within the GSTT1/GSTT2 region using PennCNV, and examined associations of the identified CNVs with preterm birth and with birth weight (BW) in full term birth controls, including interactions with SMK. Finally, we tested the association of CNVs in GSTT1/GSTT2 with SMK. We confirmed the association of smoking with low BW and PTD. We identified 2 CNVs in GSTT2 (GSTT2a and GSTT2b), 1 CNV in GSTTP1 and 2 CNVs in GSTT1 (GSTT1a and GSTT1b). The GSTT2a deletion was associated with reduced BW (-284g, p=2.5E-7) in smokers, and was more common in smokers (odds ratio[OR]=1.3, p=0.036). We found that the size of the reported common deletion CNV in GSTT1 was larger than previously shown. The GSTTP1 and GSTT1b null genotypes were in high linkage disequilibrium (LD) (D’=0.89) and less common in smokers (OR=0.68, p=0.019 and OR=0.73, p=0.055 respectively). These two deletions were in partial LD with GSTT2a and GSTT2b duplications. All 5 CNVs seem to be associated with increased risk of preterm birth before 35 completed weeks. CNVs in the GSTTT1/GSTT2 region appear associated with low BW and PTD outcomes, but LD complicated these CNVs in GSTT1/GSTT2. In genetic association studies of BW, multiple CNVs in this region need to be investigated instead of a single polymorphism.